Real-Time Monitoring of Spray Drift from Three Different Orchard Sprayers. (May 2019) - Blanco, Magali N.; Fenske, Richard A.; Kasner, Edward J.; Yost, Michael G.; Seto, Edmund; Austin, Elena
Abstract: In Washington State, half of all pesticide-related illnesses in agriculture result from drift, the off-target movement of pesticides. Of these, a significant proportion involve workers on another farm and orchard airblast applications. We compared the spray drift exposure reduction potential of two modern tower sprayers – directed air tower (DAT) and multi-headed fan tower (MFT), in relation to a traditional axial fan airblast (AFA) sprayer. We employed real-time particle monitors (Dylos DC1100) during a randomized control trial of orchard spray applications. Sections of a field were randomly sprayed by three alternating spray technologies – AFA, DAT and MFT – while monitors sampled particulate matter above and below the canopy at various downwind locations in a neighboring field. Geometric mean particle mass concentrations (PMC) outside the intended spray area were elevated during all applications at all of our sampling distances (16–74 m, 51–244 ft). After adjusting for wind speed and sampling height, the 75th percentile (95% confidence interval) PMC level was significantly greater during spray events than background levels by 105 (93, 120) μg/m 3, 49 (45, 54) μg/m 3 and 26 (22, 31) μg/m 3 during AFA, DAT and MFT applications, respectively. Adjusted PMC levels were significantly different between all three sprayers. In this study, tower sprayers significantly reduced spray drift exposures in a neighboring orchard field when compared to the AFA sprayer, with the MFT sprayer producing the least drift; however these tower sprayers did do not fully eliminate drift. Highlights: Elevated particle levels at all sampling locations 16–74 m from spray applications. Significantly lower particle levels during tower than airblast sprayer applications. Significantly higher particle levels at closer distances and below the canopy. The EPA's application exclusion zone is likely not fully protective of drift. Real-time monitoring may be an effective, novel method of drift characterization.